Critical perspectives on addiction - Netherland, Julie (Bingley, U.K. : Emerald, 2012)
Our understandings of addiction are rapidly changing. New technologies and biomedical treatments are reconfiguring addiction as a brain disease, and the concept of "addiction" is expanding to cover an ever widening array of substances and behaviours, from food to shopping. This volume looks critically at how addiction has been framed historically, how it is characterized and understood through contemporary cultural representations, how new treatments and technologies are reconfiguring addiction, and how "addiction" is being expanded beyond illicit drugs and alcohol to explain phenomena such as "excessive" eating and gambling and the exponential rise in prescription narcotic use. It also examines how medical, behavioural and punitive frameworks come together to shape and control "addicts". Featuring the work of several new, up-and-coming scholars working to deepen theoretical perspectives on addiction and its relationship to social control and deviance, this volume fills a gap in addiction studies by offering critical perspectives that interrogate and challenge traditional and/or mainstream understandings of addiction.
Medicalization and biomedicalization : does the diseasing of addiction fit the frame? / Nancy D. Campbell -- De-medicalizing addiction : toward biocultural understandings / Kerwin Kaye -- Pharmaceutical incursion on cigarette smoking at the birth of the brain disease model of addiction / Mark Elam -- Two tiers of biomedicalization : Methadone, Buprenorphine, and the racial politics of addiction treatment / Helena Hansen, Samuel K. Roberts -- Intervention : reality TV, whiteness, and narratives of addiction / Jessie Daniels -- Drawing the line at drinking for two : governmentality, biopolitics, and risk in state legislation on fetal alcohol spectrum disorders Deborah A. Potter -- Into the light : evangelical rehab and the seduction of new life / Teresa Gowan, Jack Atmore -- Making addicts of the fat : obesity, psychiatry and the 'fatties anonymous' model of self-help weight loss in the post-war United States / Jessica Parr, Nicolas Rasmussen -- 'I just couldn't keep it in control anymore' : weight loss surgery, food addiction, and anti-fat stigma / Zoë Meleo-Erwin -- Video game addiction : user perspectives / Luther Elliott, Geoffrey Ream, Elizabeth McGinsky.
Print version record
Keywords: Social Science -- Sociology -- General; Social Science -- Disease & Health Issues; Social Science -- General; Illness & addiction: social aspects; Personal & social issues: drugs & addiction (Children's/YA).; Compulsive behavior; Substance abuse; Social medicine